Specialist Embalming of Burnt Bodies in Nigeria using Porcine Analogues - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context:Embalming of burnt bodies requires special attention. It also requires the restoration of distorted body structures. The difficulty in embalming burnt decomposing bodies in Anambra state, Nigeria led to this investigation; and hence, this pilot study provided suitable embalming methodology and fluid required to arrest early bloat stage of decomposition of burnt bodies using porcine models (Sus scrofa domestica).Materials and Methods:Animals were sacrificed and allowed to reach the early bloat stage of decomposition before embalming. The outcome of embalming was scored and recorded as post-embalming body score (PBS). A Pearson correlation analysis was used to test the relationship between the outcome of embalming and independent variables (embalming fluid volume, duration of embalming, atmospheric temperature, room temperature, and humidity).Results:The results showed that the independent variables that statistically affected the outcome of embalming include duration of embalming, embalming fluid volume, and room temperature. The independent variables that did not statistically affect the outcome of embalming include humidity and atmospheric temperature.Conclusion:An embalming mixture containing formalin, methanol, thymol, and water is suitable to arrest early decomposing burnt bodies via the arterial embalming technique, which is supplemented by hypodermic embalming technique.